Strengthening Services Trade in the Malaysian Economy March 2022 - World Bank (Washington, DC, 2022)
While Malaysia’s economy has had great success, it also faces several challenges including limited services trade. This report seeks to explain the main constraints that are holding back the services sector in the country. The key finding is that Malaysia’s development strategy needs to pivot to better capture new trade patterns. This will need to address some of the main constraints facing the development of Malaysia’s services sector. First, is low labor productivity. Secondly, is informality. Thirdly, weak educational outcomes in Malaysia contribute to skills shortages. Finally, limits to competition and regulatory restrictions in services restrict Malaysia’s ability to deepen foreign linkages. The key recommendation of the report is that to fulfill the potential of its services sector, Malaysia should take an integrated approach that progressively and gradually addresses artificial policy distinctions between goods and services, and between trade and investment in a world increasingly governed by international production networks.